“Sheikh Abdurrauf Kang Abangsa Syekh Hamzah Fansuri”: Examining the Relationship Between Two - Ramli, Ramli (Journal of Islamic History and Manuscript, 2024)
The phrase "Sheikh Abdurrauf is in the same tribe as Hamzah Fansuri" in the Cirebon tripe manuscript sparked debate among researchers regarding the relationship between Sheikh Abdurrauf and Hamzah Fansuri. This debate became interesting because a collective memory was found among the people of Singkil Aceh, who believed that there was a nephew-uncle and student-teacher relationship between them. Collective memory is strengthened by two sites, which are the graves of Sheikh Ali Al Fanshuri (father of Sheikh Abdurrauf) and his younger brother, Sheikh Hamzah Fansuri, in two areas in Singkil. Through critical analysis of literature and in-depth exploration of collective memory and sites, the author concludes that the two of them had a familial relationship as nephew and uncle, and they even had a student and teacher relationship at the beginning of Sheikh Abdurrauf's education